Neighborhood Deprivation and Self-Rated Health in Lagos State, Nigeria - Ojikutu, Rasheed Kola (Dhaulagiri Journal of Sociology and Anthropology, 2008)
This study examines the effect of neighborhood deprivation on the perception of the individuals about their own health in Lagos State, Nigeria. Respondents were required to rate their own health as "excellent, very good, good, fair, poor and very poor". The questionnaire contained questions on various aspect of the respondents neighborhood and their perception about them. It was found that most neighborhoods in Lagos State are deprived of basic essentials of life such as electricity, water, good roads and security. Over 43% of the respondents claimed to have visited a hospital two or more times and 43.7% had lost at least two neighbors in the past one year. Over half (57.8%) of the respondents rated their own health as good, 36.6% ranked their own health as fair while only 5.6% claimed to have poor health. A fitted regression model ( r2 = 0.644) showed that variables such as number of dependants, income, occupation, type of residential accommodation, ownership of house, number of rooms occupied, mode and convenience of transportation, accessibility to water, electricity and good roads and security jointly determine the perception of an individual about his own health status.Key Words: Neighborhood, Deprivation, Self Rated Health, Security, ResidenceDOI = 10.3126/dsaj.v2i0.1364Dhaulagiri Journal of Sociology and Anthropology Vol.2 pp.193-210